DEK terminates diapause by activation of quiescent cells in the crustacean Artemia. Issue 12 (26th June 2019) - Jia, Wen-Huan; Li, An-Qi; Feng, Jing-Yi; Ding, Yan-Fu; Ye, Sen; Yang, Jin-Shu; Yang, Wei-Jun
Abstract : To cope with harsh environments, the Artemia shrimp produces gastrula embryos in diapause, a state of obligate dormancy, having cellular quiescence and suppressed metabolism. The mechanism behind these cellular events remains largely unknown. Here, we study the regulation of cell quiescence using diapause embryos of Artemia . We found that Artemia DEK ( Ar -DEK), a nuclear factor protein, was down-regulated in the quiescent cells of diapause embryos and enriched in the activated cells of post-diapause embryos. Knockdown of Ar-DEK induced the production of diapause embryos whereas the control Artemia released free-swimming nuaplii. Our results indicate that Ar -DEK correlated with the termination of cellular quiescence via the increase in euchromatin and decrease in heterochromatin. The phenomena of quiescence have many implications beyond shrimp ecology. In cancer cells, for example, knockdown of DEK also induced a short period of cellular quiescence and increased resistance to environmental stress in MCF-7 and MKN45 cancer cell lines. Analysis of RNA sequences in Artemia and in MCF-7 revealed that the Wnt and AURKA signaling pathways were all down-regulated and the p53 signaling pathway was up-regulated upon inhibition of DEK expression. Our results provide insight into the functions of Ar -DEK in the activation of cellular quiescence during diapause formation in Artemia .